Influence of Inventory and Product Quality on Sales Volume at PT. Bilah Baja Makmur Abadi - Elisabeth Nainggolan (Jurnal Manajemen Bisnis Eka Prasetya, 2022)
This study aims to determine the effect of Inventory on Sales Volume at PT. Bilah Baja Makmur Abadi Medan, determine the effect of Product Quality on Sales Volume at PT. Bilah Baja Makmur Abadi Medan, determine the effect of Inventory and Product Quality on Sales Volume at PT. Bilah Baja Makmur Abadi Medan. The population in this study are customers of PT. Bilah Baja Makmur Abadi Medan totaling 2.515 respondents. The technique of determining the number of samples used in this study is Slovin formula and totaling 96 respondents. The results of the research analysis show that Inventory and Product Quality partially have a positive and significant effect on Sales Volume at PT. Bilah Baja Makmur Abadi Medan. The results showed that Inventory and Product Quality simultaneously have a positive and significant effect on Sales Volume at PT. Bilah Baja Makmur Abadi Medan. The results of this study are supported by the value of R square (R2) which means Inventory and Product Quality have an effect on Sales Volume at PT. Bilah Baja Makmur Abadi Medan. While the remaining is effected by other factors originating from outside this research model such as people, process and physical evidence.